2006
DOI: 10.1002/ajim.20309
|View full text |Cite
|
Sign up to set email alerts
|

A cohort mortality study of leather tanners in Tuscany, Italy

Abstract: The study confirms previous observations among tanners of increased mortality from lung, bladder, and pancreatic cancer. Noteworthy are the increased mortality from myeloid leukemia together with the new findings of an increased mortality from endocrine glands tumors, blood diseases, and psychiatric disorders which should be considered with caution because of the small number of cases and the novelty of the observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Another difference may have been our use of RR estimates from subgroups that are more likely to be highly exposed (eg, exposure duration ≥10 years), although direct comparisons are difficult for the reason given above. We also excluded five studies used by Gatto et al because they were unpublished, involved painters or foundry workers with uncertain exposure,24 25 or overlapped with the already included studies 26 27. However, adding these five excluded studies to our meta-analysis of all studies caused little change (1.27; 95% CI 1.18 to 1.37) since most of these studies only received a small amount of the total weighting.…”
Section: Discussionmentioning
confidence: 99%
“…Another difference may have been our use of RR estimates from subgroups that are more likely to be highly exposed (eg, exposure duration ≥10 years), although direct comparisons are difficult for the reason given above. We also excluded five studies used by Gatto et al because they were unpublished, involved painters or foundry workers with uncertain exposure,24 25 or overlapped with the already included studies 26 27. However, adding these five excluded studies to our meta-analysis of all studies caused little change (1.27; 95% CI 1.18 to 1.37) since most of these studies only received a small amount of the total weighting.…”
Section: Discussionmentioning
confidence: 99%
“…Co-exposure to other carcinogens, such as silica was discussed by authors with respect to lung cancer SMRs, as was possible confounding by tobacco smoking. Iaia et al [41] reported an SMR of 2.08 (95% CI = 0.05, 11.61) based on one case among Italian leather tanners who were possibly exposed to Cr(VI) in leather pigments. The authors noted that some of the pigments used were lead-based, as well as that co-exposures to numerous other chemicals are prevalent in the tanning industry.…”
Section: Small Intestine Cancermentioning
confidence: 96%
“…A number of other substances or complex compounds are probable or possible lung carcinogens, for example, welding fumes, lead, vinyl chloride, non arsenical insecticides [1,2]. Elevated lung cancer risks have also been found in several occupations or industries, particularly among painters [2] and, less consistently, in the rubber industry [3], among butchers [4], hairdressers [5], woodworkers [6], leather workers [7] and printers [8,9]. …”
Section: Introductionmentioning
confidence: 99%